SAPs as novel regulators of abiotic stress response in plants. (2nd May 2013) - Giri, Jitender; Dansana, Prasant K.; Kothari, Kamakshi S.; Sharma, Gunjan; Vij, Shubha; Tyagi, Akhilesh K.
<x xml:space="preserve">Abstract</x> Stress associated proteins (SAPs), novel A20/AN1 zinc‐finger domain‐containing proteins, are fast emerging as potential candidates for biotechnological approaches in order to improve abiotic stress tolerance in plants – the ultimate aim of which is crop‐yield protection. Until relatively recently, such proteins had only been identified in humans, where they had been shown to be key regulators of innate immunity. Their phylogenetic relationship and recruitment of diverse protein domains reflect an architectural and mechanistic diversity. Emerging evidence suggests that SAPs may act as ubiquitin ligase, redox sensor, and regulator of gene expression during stress. Here, we evaluate the new knowledge on SAPs with a view to understand their mechanism of action. Furthermore, we set an agenda for investigating hitherto unexplored roles of these proteins.